2005
DOI: 10.1016/j.cell.2005.09.021
|View full text |Cite
|
Sign up to set email alerts
|

α-Catenin Is a Molecular Switch that Binds E-Cadherin-β-Catenin and Regulates Actin-Filament Assembly

Abstract: Epithelial cell-cell junctions, organized by adhesion proteins and the underlying actin cytoskeleton, are considered to be stable structures maintaining the structural integrity of tissues. Contrary to the idea that alpha-catenin links the adhesion protein E-cadherin through beta-catenin to the actin cytoskeleton, in the accompanying paper we report that alpha-catenin does not bind simultaneously to both E-cadherin-beta-catenin and actin filaments. Here we demonstrate that alpha-catenin exists as a monomer or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
848
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 898 publications
(893 citation statements)
references
References 56 publications
(85 reference statements)
38
848
1
6
Order By: Relevance
“…b-catenin, p120 and VE-cadherin form a complex. Formation of this ternary complex stabilizes the adherens junction 38 . Distance of adherens junction is at least 22.5 nm.…”
Section: Methodsmentioning
confidence: 99%
“…b-catenin, p120 and VE-cadherin form a complex. Formation of this ternary complex stabilizes the adherens junction 38 . Distance of adherens junction is at least 22.5 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Recent studies have revealed the surprising fact that cadherins are necessary for the early recognition of neighboring cells during mesenchymalepithelial transition, whereas a-catenin and the actin cytoskeleton are more important in the maintenance of an epithelial phenotype. [7][8][9] On the basis of these observations it is obvious that linkages between the components of adherens junctions (AJ), a-catenin, b-catenin, p120catenin, a-actinin and vinculin, are targets of complex signalling mechanisms regulated by Rho family GTPases, and various kinases and phosphatases. 10 In addition to cell-cell contacts, integrinmediated cell-ECM contacts are crucial for the differentiation of epithelial cells.…”
mentioning
confidence: 99%
“…Interestingly, we observed changes in the genes underlying cytoskeletal architecture; namely dynein complex, ephrin b, cadherin, and integrin genes were more highly expressed in dyskinetic rats compared to both untreated parkinsonian controls and non-dyskinetic animals. Cadherins and catenins, along with Arc, are known to interact with and alter the actin cytoskeleton structure (Tanaka et al, 2000;Drees et al, 2005); Figure 5). We propose that this increase in transcription may indicate a mechanism for the previously observed increase in the number of synapses in dyskinetic animals (Zhang et al, 2013;Fieblinger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%